PROFIL ASAM LEMAK IKAN TUNA (THUNNUS, SP.) ASAP SELAMA PERENDAMAN DENGAN ASAP CAIR WAA SAGU - Amahorseja, Anggeline L. (Hibualamo : Seri Ilmu-Ilmu Alam dan Kesehatan, 2018)
ABSTRAK Penelitian ini bertujuan untuk menentukan profil asam lemak dari Ikan Tuna (Thunnus, sp.) Asap dengan perendaman pada asap cair Waa Sagu. Hasil analisis profil asam lemak pada ikan tuna (Thunnus, sp.) asap dengan perendaman pada asap cair Waa Sagu, terdeteksi 27 puncak kromatogram Lauric acid (C12:0), Myristic acid (C14:0), Myristoleic acid (C14:1), Pentadecanoic acid (C15:0), Palmitic acid (C16:0), Palmitoleic acid (C16:1), Heptadecanoic acid (C17:0), Stearic acid (C18:0), Elaidic acid (C18:1n9t), Oleic acid (C18:1n9c), Linoleic acid (C18:2n6c), Arachidic acid (C20:0), ?- linolenic acid (C18:3n6), Cis- 11 ? Eicosenoic acid (C 20:1), Linolenic acid (C18:3n3), Heneicosanoic acid (C21:0), Cis-11,14-Eicosedienoic acid (C20:2), Behenic acid (C22:0), Cis-8, 11, 14- Eicosetrienoic acid (C20:3n6), Cis-11,14,17- Eicosetrienoic acid (C20:3n3), Arachidonic acid (C20:4n6), Tricosanoic acid (C23:0), Cis-13,16-Docosadienoic acid (C22:2), Lignoceric acid (C24:0), Cis-5,8,11,14,17-Eicosapentaenoic acid (C20:5n3), Nervonic acid (C24:1), Cis-4,7,10,13,16,19- Docosahexaenoic acid (C22:6n3). Komposisi total asam lemak pada Ikan Tuna (Thunnus, sp.) asap dengan perendaman asap cair Waa Sagu adalah sebesar 75,73%. Ikan Tuna (Thunnus, sp.) asap mengandung 11 asam lemak jenuh (SAFA) dan 17 asam lemak tak jenuh dengan pembagian sebagai berikut: Asam Lemak Tak Jenuh Tunggal (MUFA) sebanyak 7 jenis, Asam Lemak Tak Jenuh Jamak (PUFA) sebanyak 10 jenis. Komposisi asam lemak omega 3 EPA dan DHA pada Ikan Tuna (Thunnus, sp.) asap dengan perendaman pada asap cair Waa Sagu sebesar 5,28% dan 24,67%.   This study aims to determine the fatty acid profile of Tuna (Thunnus, sp.) smoke fish by soaking in the liquid smoke of sago?s waa. Result of fatty acid profile analysis on tuna (Thunnus, sp.) smoke fishby soaking in the liquid smoke of sago?s waa, detected 27 peak chromatogram Lauric acid (C12:0), Myristic acid (C14:0), Myristoleic acid (C14:1), Pentadecanoic acid (C15:0), Palmitic acid (C16:0), Palmitoleic acid (C16:1), Heptadecanoic acid (C17:0), Stearic acid (C18:0), Elaidic acid (C18:1n9t), Oleic acid (C18:1n9c), Linoleic acid (C18:2n6c), Arachidic acid (C20:0), ?- linolenic acid (C18:3n6), Cis- 11 ? Eicosenoic acid (C 20:1), Linolenic acid (C18:3n3), Heneicosanoic acid (C21:0), Cis-11,14-Eicosedienoic acid (C20:2), Behenic acid (C22:0), Cis-8, 11, 14- Eicosetrienoic acid (C20:3n6), Cis-11,14,17 - Eicosetrienoic acid (C20:3n3), Arachidonic acid (C20:4n6), Tricosanoic acid (C23:0), Cis-13,16-Docosadienoic acid (C22:2), Lignoceric acid (C24:0), Cis-5,8,11,14,17-Eicosapentaenoic acid (C20:5n3), Nervonic acid (C24:1), Cis-4,7,10,13,16,19- Docosahexaenoic acid (C22:6n3). Total composition of fatty acids in Tuna (Thunnus, sp.) smoke by soaking in the liquid smoke of  sago?s waa was 70.89%. Tuna (Thunnus, sp.) smoke fish contains 11 saturated fatty acids (SAFA) and 17 unsaturated fatty acids with the following divisions: Mono Unsaturated Fatty Acids (MUFAs) of 7 species, Poly Unsaturated Fatty Acids (PUFAs) type. The composition of omega 3 fatty acids EPA and DHA in Tuna (Thunnus, sp.) smoke fish by soaking in the liquid smoke of eucalyptusare 5,28% and 24,67%.